A protective role of HTLV-1 gp46-specific neutralizing and antibody-dependent cellular cytotoxicity-inducing antibodies in progression to adult T-cell leukemia (ATL) - Tanaka, Yuetsu; Tanaka, Reiko; Imaizumi, Naoki; Mizuguchi, Mariko; Takahashi, Yoshiaki; Hayashi, Masaki; Miyagi, Takashi; Uchihara, Junnosuke; Ohshiro, Kazuiku; Masuzaki, Hiroaki; Fukushima, Takuya (Frontiers in Immunology, 2022)
Human T-cell leukemia virus type-1 (HTLV-1) establishes a long-term persistent infection in humans and causes malignant T-cell leukemia, adult T-cell leukemia (ATL). HTLV-1-specific cytotoxic T lymphocytes have been suggested to play a major role in the immunosurveillance of HTLV-1-infected T cells. However, it remains unclear whether HTLV-1-specific functional antibodies are also involved in the host defense. To explore the role of antibodies in the course of HTLV-1 infection, we quantitated HTLV-1-specific neutralizing and antibody-dependent cellular cytotoxicity (ADCC)-inducing antibody levels in plasma from asymptomatic carriers (ACs) and ATL patients. The levels of neutralizing antibodies, as determined by a syncytium inhibition assay, were significantly lower in acute and chronic ATL patients than in ACs. The levels of ADCC-inducing activity were tested using an autologous pair of HTLV-1-producing cells and cultured natural killer (NK) cells, which showed that the ADCC-inducing activity of IgG at a concentration of 100 µg/ml was comparable between ACs and acute ATL patients. The anti-gp46 antibody IgG levels, determined by ELISA, correlated with those of the neutralizing and ADCC-inducing antibodies. In contrast, the proviral loads did not correlate with any of these antibody levels. NK cells and a monoclonal anti-gp46 antibody reduced the number of HTLV-1 Tax-expressing cells in cultured peripheral blood mononuclear cells from patients with aggressive ATL. These results suggest a protective role for HTLV-1 neutralizing and ADCC-inducing antibodies during the course of HTLV-1 infection.